The Federal Democratic Republic of Ethiopia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper investigates the macroeconomic impact of existing gender gaps in Ethiopia and discusses the authorities' policies in the areas of gender equality and women's rights, with a focus on women's economic engagement. Ethiopia has shown a firm political commitment to the advancement of gender equality and women's rights; however significant challenges around women's economic participation remain. Whilst most people work in Ethiopia, women face many barriers to formal labor force participation, have lower levels of education than men-particularly at secondary and tertiary levels-and have significant wage gaps compared to men. The findings suggest that, eliminating gender gaps in both educational attainment and the rate of formal employment could increase output in Ethiopia over time by over 24 percent. Improved institutional capacity would lead to better integration of gender issues into the planning and implementation of government policies. Ethiopia has already embedded gender units within the structure of many of its ministries.